Application of innovative learning models in responding to learning motivation and optimizing students' HOTS - Abdulrahim Maruwae; Rierind Koniyo; Ratna Ahmad; Pebriyanti Habibu; Sriwanda Bouato (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Several phenomena that need to be addressed in economic learning, such as the tendency of differences in learning motivation in each student accompanied by problem-solving skills that still need to be accustomed to, show that the achievement of HOTS for them is still far from expectations. Responding to these conditions, an in-depth study is needed to implement an innovative learning model by paying attention to the differences in learning motivation in each student. This study was undertaken in experimental research by conducting trials of different innovative learning models, with the hope of accommodating differences in learning motivation that arise during learning. In the interest of this research, the Project Based Learning model and the Guided Inquiry learning model were determined. Both learning models are innovative learning models of the 21st century that are often recommended in learning in various curricula that apply today. This innovative learning model also has the potential to trigger the achievement of HOTS for students. This study uses a quantitative method with a type of pseudo-experiment (pseudo-experiment) which involves 3 variables, namely independent variables, attribute variables and non-free variables (bound). In this design, each variable has two levels, namely the learning model (A) as a treatment-free variable, which consists of the Project Based Learning (A1) model and the Guided Inquiry (A2) learning model. Furthermore, learning motivation (B) as an attribute variable consisting of high learning motivation (B1) and low learning motivation (B2). While the bound variable is students' critical thinking in economics subjects. This critical thinking will be analyzed based on student learning motivation data after being sorted from the highest to the lowest data in each treatment group using the applicable rules. The design of this study used a treatment analysis by level 2x2. The results of a research study based on several tests conducted showed that there was a significant interaction between innovative learning models and the level of learning motivation on students' HOTS achievement. The effectiveness of learning models in increasing HOTS differs between students with high learning motivation and students with low learning motivation. For students with high learning motivation, it is recommended to use the Project-Based Learning (PjBL) learning model in economic learning. Meanwhile, in students with low learning motivation, the Guided Inquiry learning model tends to be more effective than the PjBL learning model.